2007
DOI: 10.1080/00207160701356365
|View full text |Cite
|
Sign up to set email alerts
|

Efficientd-multigrid preconditioners for sparse-grid solution of high-dimensional partial differential equations

Abstract: Fast and efficient solution techniques are developed for high-dimensional parabolic partial differential equations (PDEs). In this paper we present a robust solver based on the Krylov subspace method Bi-CGSTAB combined with a powerful, and efficient, multigrid preconditioner. Instead of developing the perfect multigrid method, as a stand-alone solver for a single problem discretized on a certain grid, we aim for a method that converges well for a wide class of discrete problems arising from discretization on v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…So, in principle, we would expect the asymptotic theoretical optimal sparse grid convergence of O(h 2 (log h −1 ) d−1 ). However, for the multi-dimensional Poisson equation and a smooth solution, bin Zubair et al (2007) showed that the theoretical sparse grid convergence was only achieved on relatively fine grids. Here we have the same situation.…”
Section: Sparse Grid Computationsmentioning
confidence: 99%
“…So, in principle, we would expect the asymptotic theoretical optimal sparse grid convergence of O(h 2 (log h −1 ) d−1 ). However, for the multi-dimensional Poisson equation and a smooth solution, bin Zubair et al (2007) showed that the theoretical sparse grid convergence was only achieved on relatively fine grids. Here we have the same situation.…”
Section: Sparse Grid Computationsmentioning
confidence: 99%
“…[5,18,20]) have grown in popularity in recent years and are widely used for the numerical solution of PDEs. Other authors have considered different hierarchical and multigrid schemes for a variety of option pricing problems [10,15,22]. The first two of these papers develop sophisticated multilevel stand-alone solvers, while the last also considers using a custom-made multilevel method as a preconditioner.…”
Section: Introductionmentioning
confidence: 99%
“…They are used either as preconditioners [1,11,12,15,16] or within real multigrid schemes [2,3,6,26,33]. We first note that certain problems allow for sparse grid dis-S53 2.1.…”
mentioning
confidence: 99%